PENGARUH KOMPENSASI LANGSUNG DAN KOMPENSASI TIDAK LANGSUNG TERHADAP MOTIVASI KERJA KARYAWAN PT. MITRA OGAN KABUPATEN OGAN KOMERING ULU - Anwar, Rani; Kasnadian, Nopri (Jurnal Ilmu Manajemen, 2018)
The study aims to determine the effect of direct compensation and indirect compensation on employee motivation PT. Mitra Ogan Plantation Kab OKU. Data analysis was done by using multiple linear regression. After the research obtained partial results proved that direct compensation does not affect the employee's motivation at PT. Mitra Ogan Plantation Kab OKU which can be seen from t count less than t table and indirect compensation have an effect on to employee work motivation at PT. Mitra Ogan Plantation Kab OKU which can be seen from t count result is bigger than t table. Simultaneously direct compensation and indirect compensation have a affect to the employee's motivation at PT. Mitra Ogan Plantation Kab OKU that can be seen from the results f count is greater than f table. The result of coefficient of determination analysis (R Squere) is 0,327. It shows that 32,7% variation from work motivation (Y) can be explained by direct compensation variable (X1) and indirect compensation indirect compensation (X2) while the rest equal to 67.3% influenced by other variables in addition to variables in this study such as the ability / competence of employees.